1987
DOI: 10.1267/ahc.20.557
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of radioactive carbon from L-(U-14C)tyrosine in mice.

Abstract: Tissue and organ distribution of radioactive carbon from 14C-tyrosine in the mouse was studied by whole-body autoradiography and biochemical analysis. The mice injected intravenously with L-[U-14C]tyrosine were sacrificed at various intervals. Examination of autoradiographs disclosed that the injected 14C-tyrosine was rapidly taken up from the blood by the tissues. The radioactivity in the pancreas was the highest and predominant throughout the intervals after injection in this investigation.The comparative va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
1

Year Published

1989
1989
2001
2001

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
(29 reference statements)
2
2
1
Order By: Relevance
“…The finding at 180 min after injection indicates that most of the radioactive substances remained as proteins in the organs at this time. This finding that the pancreas had the highest radioactivity during the intervals tested is consistent with other reports about glutamine (3), tryptophan (8) and tyrosine (9), and different from those about methionine (1) and aspartic acid (16). This may imply the differences of the pool size of amino acids and/or the requirement for protein synthesis in the pancreas.…”
Section: Resultssupporting
confidence: 89%
See 4 more Smart Citations
“…The finding at 180 min after injection indicates that most of the radioactive substances remained as proteins in the organs at this time. This finding that the pancreas had the highest radioactivity during the intervals tested is consistent with other reports about glutamine (3), tryptophan (8) and tyrosine (9), and different from those about methionine (1) and aspartic acid (16). This may imply the differences of the pool size of amino acids and/or the requirement for protein synthesis in the pancreas.…”
Section: Resultssupporting
confidence: 89%
“…In this investigation, most of the radioactivity in the pancreas may be responsible for that in the exocrine part of this organ, as several investigators (3,12) reported that there was a high concentration of radioactivity in the exocrine part of this organ but little or no radioactivity in the islands of Langerhans. The general pattern of the autoradiographs obtained after injection of radioactive arginine had a resemblance to those reported about tryptophan (8) and other amino acids (9,12,16), and was different from those about hexoses (14,25) and hexosamines (10,11).…”
Section: Resultscontrasting
confidence: 58%
See 3 more Smart Citations